Atomistic modeling of graphene/hexagonal boron nitride polymer nanocomposites: a review. (13th November 2017) - Verma, Akarsh; Parashar, Avinash; Packirisamy, M.
Abstract : Due to their exceptional properties, graphene and hexagonal boron nitride (h‐BN) nanofillers are emerging as potential candidates for reinforcing the polymer‐based nanocomposites. Graphene and h‐BN have comparable mechanical and thermal properties, whereas due to high band gap in h‐BN (~5 eV), have contrasting electrical conductivities. Atomistic modeling techniques are viable alternatives to the costly and time‐consuming experimental techniques, and are accurate enough to predict the mechanical properties, fracture toughness, and thermal conductivities of graphene and h‐BN‐based nanocomposites. Success of any atomistic model entirely depends on the type of interatomic potential used in simulations. This review article encompasses different types of interatomic potentials that can be used for the modeling of graphene, h‐BN, and corresponding nanocomposites, and further elaborates on developments and challenges associated with the classical mechanics‐based approach along with synergic effects of these nano reinforcements on host polymer matrix. This article is categorized under: Molecular and Statistical Mechanics > Molecular Mechanics Structure and Mechanism > Computational Materials Science Molecular and Statistical Mechanics > Molecular Dynamics and Monte‐Carlo Methods Abstract : Atomistic modeling of graphene/h‐BN nanocomposites.